Evaluation of Contamination of Poultry Meat and Semi-finished Products with Campylobacter Bacteria (Asian Journal of Pharmaceutics (AJP), 2017)
Purpose: The scope of the paper was the assessment of the contamination (or monitoring) of poultry meat and semi-finished products with Campylobacter (â€œfrom the retail network and farmsâ€ may be added), using the culture identification technique and the polymerase chain reaction method, as well as the evaluation of the antibiotic resistance of strains isolated from poultry meat and semi-finished products. Materials and Methods: The experimental part of the work was carried out on the basis of the Institute of Veterinary and Sanitary Expertise, Biological and Food Safety of the Moscow State Institute of Food Production and the Federal Publicly Funded Institution of Science â€œFIC of Nutrition and Biotechnologyâ€ at the Nutriicrobiome Biosafety and Analysis Laboratory. The GOST ISO 10272-1-2013 â€œmicrobiology of food and animal feeds. Methods for the detection and counting of Campylobacter spp., Part 1. Detection methodâ€ was used in the work performed to isolate and identify the Campylobacter spp., Pure growths were identified per totality of cultural, morphological, and biochemical signs confirming the belonging of the isolated cultures to the bacteria of the Campylobacter genus. The belonging of Campylobacter spp., isolated cultures was also determined by polymerase chain reaction (PCR) with electrophoretic detection of amplification products in an agarose gel. The sensitivity to antibiotics was determined according to the clinical guidelines â€œdetermination of the sensitivity of microorganisms to antimicrobial agentsâ€ (IACMAC, 2014) by disc diffusion method using standard discs. Results: It was established that out of the 28 samples of poultry meat and semi-finished products, Campylobacter bacteria were found in 4 samples of the half-finished product â€œdrumetteâ€ in the weights of 10 and 1.0 g. Conclusions: The results of the PCR analysis confirmed the belonging of the isolated cultures to Campylobacter Jejuni species. In turn, the PCR is a faster method than the culture technique and allows giving a definitive answer within a few hours.